(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Arko PF, Sudirman LI, Qayim I. 2021. Changes in landscape ecology between nature reserve and palm oil plantation in West Java, Indonesia based on the observations of macrofungal population. Biodiversitas 22: 4526-4537. As the biggest tropical country in Southeast Asia with the third-largest forest, Indonesia has limited data on macrofungal diversity. The limitation of the data is due to the lack of study on macrofungi in high biodiversity locations such as Dungus Iwul Nature Reserve (CADI). The purpose of this study was to determine and analyze the population of macrofungal species caused by the conversion in landscape structure (fragmentation and land-use change) that occurred in CADI patch and oil palm plantation of PT Perkebunan Nusantara VIII (PTPN) matrix, Cigelung, West Java. The sampling method used was opportunistic sampling assisted by line intercept. The macrofungal identification was based on morphological characters. The analysis of community ecology was performed in R programme. The results showed that macrofungal population and diversity in CADI were the highest, followed by PTPN planted in 2004 and planted in 2003, with a significant difference among the three study locations. The community dominance index shows the opposite, with the highest in PTPN 2003 and the lowest in CADI. These results showed changes in macrofungal population and diversity from the conversion in landscape structure. There were eleven indicator species in CADI, two species in PTPN 2003, and five species in PTPN 2004.